Implementation of Multicultural Education As Revitalization of National Awareness for Sociology Education Students - Jalal Jalal (AL-ISHLAH: Jurnal Pendidikan, 2024)
Despite the optimism of many scholars, activists, and educators for a fully multicultural world, the aims of people of colour and multiculturalists are still hindered by social problems such as racism, inequality, injustice, and poverty. This research aims to explore multicultural education in a nation that is becoming more aware, specifically focusing on students studying sociology education. The study method adopts a qualitative phenomenological approach that focuses on comprehending the significance of different experiences and human interactions. It is crucial to cultivate an understanding of students' sociology education in order to promote awareness of intercultural marriages in both academic and non-academic settings. Resistance to implementing intercultural education is present both within the organisation and from external sources. Multiculturalism aids students in understanding and valuing the various aspects of culture, language, ethnicity, religion, and race that contribute to the Indonesian nation, which is essential for the formation of national identity. Multicultural education theorists and policymakers in universities should challenge assumptions about ethnic and cultural dominance and promote the inclusion of the Indonesian language in multicultural education.